SPORTS HYGIENE, MODE AND IMPORTANCE OF SLEEP (Conferencea, 2023)
The hygiene of physical education and sports is the science of the impact of various factors related to physical culture and sports on the health of the athletes: environmental conditions where physical exercises are performed; the content and organization of physical exercises; the volume and intensity of physical exertion during physical training; the nature of food; Sportsman's technical equipment and outfit. Based on the study of the influence of these factors, I am developing hygienic recommendations, norms and rules.